FORMATION OF YOUNG STUDENTS’ VALUE ATTITUDE TO PSYCOLOGICAL HEALTH DURING EXTRACURRICULAR ACTIVITIES MEANS ART THERAPY - Muromets, Victoria H. (Educological discourse, 2014)
The article deals with the formation of the valuable relation to the psychological health of students; carried out a theoretical analysis of the concept of «psychological health of the individual»; revealed the potential of the art therapy in extracurricular activities as a preventive factor preventing negative impacts of modern society on the psychological health of the individual.